2022
DOI: 10.7150/ijbs.65802
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-dependent macrophage-to-fibroblast signaling contributes to cardiac diastolic dysfunction in heart failure with preserved ejection fraction

Abstract: Rationale: Heart failure with preserved ejection fraction (HFpEF) can arise from hypertension-induced cardiac remodeling. Monocyte/macrophage accumulation and inflammation are crucial elements in the pathogenesis of hypertension-induced cardiac remodeling. The C-X-C chemokine receptor 4 (CXCR4) is a critical regulator of the macrophage-mediated immune response. Nevertheless, the contribution of CXCR4 to macrophage phenotype and function during the progression of HFpEF remains unclear. Herein, we aimed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…For instance, in an HFpEF mouse model constructed by salty drinking water/unilateral nephrectomy/aldosterone or macrophages, major infiltrating inflammatory cells in the heart expressed CXCR4 in large numbers. The high expression of CXCR4 can inhibit peroxisome proliferator‐activated receptor γ activity, enhance the pro‐inflammatory state of macrophages, and also fuel CXCL3 expression to promote myofibroblast differentiation and fibrosis 35 . Inhibition of the C‐C motif chemokine ligand (CCL)2/C‐C motif chemokine receptor (CCR)2 axis can improve cardiac dysfunction and delay fibrosis in the TAC mouse model 36 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in an HFpEF mouse model constructed by salty drinking water/unilateral nephrectomy/aldosterone or macrophages, major infiltrating inflammatory cells in the heart expressed CXCR4 in large numbers. The high expression of CXCR4 can inhibit peroxisome proliferator‐activated receptor γ activity, enhance the pro‐inflammatory state of macrophages, and also fuel CXCL3 expression to promote myofibroblast differentiation and fibrosis 35 . Inhibition of the C‐C motif chemokine ligand (CCL)2/C‐C motif chemokine receptor (CCR)2 axis can improve cardiac dysfunction and delay fibrosis in the TAC mouse model 36 .…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is a chemokine receptor that is expressed in cardiomyocytes, fibroblasts and endothelial cells, mediates homing of progenitor cells, is involved in cell proliferation, migration and survival; and has been identified as a hub gene in human HCM [26,71,72,75,76]. In a mouse model of heart failure with preserved ejection fraction, increased CXCR4-positive macrophages were found in the circulation and the myocardium, which was associated with myofibroblast differentiation, fibrosis and an increased in inflammatory cytokines [77]. The gene expression for the chemokines MIF and CXCL12, which are the main CXCR4 ligands, were reduced in the HCM LV.…”
Section: Plos Onementioning
confidence: 99%
“…Alternatively, cardiac fibrosis was proposed to be favored by EC activation, which subsequently led to inflammatory cells infiltration in the heart. Both macrophage-derived Interleukin-10 (IL-10) (Zhang N. et al, 2022) and T-cell derived Interleukin-18 (IL-18) (Yu et al, 2009) were shown to promote cardiac fibroblast activation. Besides, lymphocytes were shown to be necessary for cardiac fibrosis and diastolic dysfunction (increased EDP) in HFD-fed mice using SCID mice (Zibadi et al, 2010).…”
Section: Fibrosismentioning
confidence: 99%
“…Macrophages via Il-10 production (Zhang N. et al, 2022) and neutrophils via neutrophil extracellular traps (NETs) (Zhang X.-L. et al, 2022) were shown to promote diastolic dysfunction (increased EDP and Tau) in a mouse model of hypertension induced by salty drinking water, unilateral nephrectomy, and chronic exposure to aldosterone. We have shown that mast cells via histamine release promote diastolic dysfunction (increased EDP) in Lerp db/db mice (Guimbal et al, 2021).…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation